The effectiveness of Kementerian Perdagangan Dalam Negeri, Koperasi Dan Kepenggunaan (KDNKK) Kota Kinabalu program on Price Control and Anti-profiteering Acts 2011 for goods suppliers in Kota Kinabalu, Sabah / Mohd Sabri Metan - Metan, Mohd Sabri (2015)
This research is to study the effectiveness of KPDNKK Kota Kinabalu program on Price Control and Anti-Profiteering Acts towards goods suppliers who participated or were invited to this program. In this study, the researcher found 4 (four) independent variables which were related to the study. The independent variables were date and time of the program, location of the program, facilities used for the program and facilitator's skills. The findings showed that the location of the event has no positive relationship towards the dependent variable while the other three independent variables which were date and time, facilities and facilitator's skills have positive relationships with the effectiveness of KPDNKK program on price control and antiprofiteering act 2011 towards goods suppliers in Kota Kinabalu Sabah. The researcher also found that most of the respondents understood the Price Control and Anti-Profiteering Acts 2011 based on the data gathered.